The outcasts - Flanagan, John (John Anthony) (New York : Philomel Books, 2011)
Hal, Stig, and the other outcasts do not have the size and strength of the Skandians, but when they face off against the Wolves and the Sharks in an ultimate race for survival, they hope that their courage and cunning are enough to help them win in a game that everyone seems to think is a matter of life and death.
School Library Journal, February 2012
Booklist starred, November 2011
Publisher's Weekly, October 2011
5.9
5-8
Keywords: Outcasts -- Juvenile fiction; Racing -- Juvenile fiction; Heroes -- Juvenile fiction; Friendship -- Juvenile fiction; Outcasts -- Fiction; Racing -- Fiction; Heroes -- Fiction; Friendship -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Outcasts -- Fiction; Racing -- Fiction; Heroes -- Fiction; Friendship -- Fiction; Adventure fiction; Fantasy fiction; Adventure fiction; Fantasy fiction